Angiospermic plant diversity of Subarnachar upazila in Noakhali, Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The present study has been carried out for the inventory and documentation of the angiospermic plant diversity of Subarnachar Upazila under Noakhali district of Bangladesh. A total of 345 angiosperm species under 257 genera belonging to 87 families has been documented from the study area during March 2010 to October 2012. Of these, Magnoliopsida is represented by 208 genera and 283 species under 68 families, whereas Liliopsida is represented by 49 genera and 62 species under 19 families. In Magnoliopsida, Fabaceae appeared to be the largest family having with 23 species whereas in Liliopsida, Poaceae appeared to be the largest family having with 16 species. Habit analysis showed that herbs, shrubs, trees and climbers were represented by 174, 53, 96 and 22 species respectively. Maximum flowering and fruiting period were recorded in spring (28%) and minimum in summer (12%).J. Asiat. Soc. Bangladesh, Sci. 40(1): 39-60, June 2014